The impact of skilled workforce migration on Emerging technologies in Afghanistan (Salam International Academic Journal, 2026)
The mass migration of Afghanistan’s skilled IT workforce since 2021 has had profound consequences on the country’s technological infrastructure and capacity for innovation. This paper investigates the multidimensional impact of this brain drain, with a particular focus on enterprise systems, software development, computer science education, and the adoption of emerging technologies. Using case studies such as the failed Oracle Solaris migration at Kabul Bank and institutional data from Afghan universities and public sector databases, we demonstrate how the loss of over 70% of certified IT professionals has led to systemic failures, stalled projects, increased cybersecurity risks, and a weakened talent pipeline. Beyond assessing the damage, this study also explores strategic responses to mitigate the effects of workforce migration. Recommended solutions include strengthening STEM education, incentivizing talent retention and return migration, fostering public-private partnerships, improving digital infrastructure, and promoting remote collaboration with the Afghan diaspora. The research concludes that while the challenges are severe, a coordinated, multi-stakeholder approach rooted in policy reform, investment, and international collaboration can help Afghanistan rebuild a resilient, self-sustaining tech ecosystem and reclaim its position in the global technological landscape.
Keywords: Emerging technologies; Enterprise systems; Software development; Cybersecurity; Digital infrastructure; Oracle Solaris